Impact of universal irradiation on chronic transfusion for sickle cell disease. Issue 8 (12th July 2021) - Salinas Cisneros, Gabriel; Webb, Jennifer; Luban, Naomi L. C.; Nickel, Robert Sheppard
Abstract: Background: Irradiation of blood products prevents transfusion‐associated graft‐versus‐host disease, but most patients do not require this modification which could have an adverse impact on transfusion outcomes. We hypothesized that irradiation may increase transfusion requirements for patients with sickle cell disease (SCD) receiving chronic transfusion. Study Design and Methods: Our pediatric hospital implemented a new policy of universal blood product irradiation in May 2018. We conducted a retrospective chart review of patients with SCD receiving chronic red blood cell (RBC) transfusion throughout the year before and after institution of this policy. The primary outcome was the change in RBC transfusion volume per patient weight transfused during the pre‐ vs. post‐ universal irradiation period. Secondary outcomes were the change in median pretransfusion laboratory values. Results: Among 17 patients, 8 (47%) received more RBCs the year before irradiation and 9 (53%) received more the year after irradiation. Implementation of universal irradiation did not significantly increase transfusion volumes needed to clinically manage this population (median change +1.7 ml/kg/year, p = .54). Additionally, there were no significant changes in absolute reticulocyte count, hemoglobin, hemoglobin S%, white blood cell count, lactate dehydrogenase, total bilirubin, serum potassium, and ferritin during the two time periods. Conclusion: In a cohort of patients with SCD receiving simple chronic transfusion, irradiation did not impact transfusion requirements or pertinent pretransfusion laboratory values. Irradiation does not appear to have clinically significant consequences for SCD chronic transfusion management.